Effect of seed priming on physiological and agronomic traits of sunflower genotypes under different irrigations - Abbasi, Z. A.; Kandhro, M. N.; Chachar, Q.; Shah, A. N.; Memon, H. R.; Chachar, S.; Mangrio, N. (International Journal of Agricultural Technology, 2021)
Seed priming with nutrients improves germination of seed, establishment of seedling as well as growth of crop and oil content. Irrigation is one of the most significant aspects to facilitate necessary for accurate crop growth, constant improvement and superior yield and oil content of sunflower. Water deficit affects growth of plant and oil content. The field experiments were carried out at Students’ Experimental Farm, Sindh Agriculture University, Tandojam for two years throughout autumn 2017 and 2018. Treatments for priming had significantly influenced on germination of seeds (m-2), rate of crop growth (g m-2 day-1), stem girth (cm), achene head-1, (1000-achenes wt., g), achene yields (t ha-1) and % of oil content. The influence of irrigation frequencies was found considerable in all traits. Interaction was initiated also significant in all parameters, except seed germination (m-2). Priming of seed with 0.2% ZnSO4 showed higher (6.3 m-2) germination, crop growth rate (1.8 g m-2 day-1), stem girth (7.1cm), achene head-1 (833), (1000-achenes wt., (66.5 g), achene yields (2.01 t ha-1) and oil content (38.1%) than the control. Irrigation frequency five also influenced on all parameter which produced maximum output more than other irrigations. Thus, it is concluded that use of 0.2% ZnSO4 priming along with five irrigations gave maximum physiological and agronomic traits. Sunflower variety HO-1 may be preferred for better oil performance under agro-climate of Tandojam, Sindh, Pakistan